Pengaruh Pendapatan Asli Desa dan Alokasi Dana Desa Terhadap Kemandirian Keuangan Desa di Kabupaten Trenggalek - Desi Nuryatul Safitri; Lantip Susilowati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to examine village original income and allocation of village funds as factors affecting village financial independence in Trenggalek Regency. The research approach used is a quantitative approach. The data used is secondary data in the form of aAPBDes realization report of the Trenggalek Regency for the 2020 period. The data was obtained from the Trenggalek Regency Community and Village Empowerment Service. The population in this study amounted to 152 villages covering all villages located in Trenggalek Regency. From the total population, a saturated sample is taken (total sampling) with the aim that the information obtained is accurate. Some of the data obtained by the researcher contains extreme data that must be removed (outliers), so that the total sample used is 127 samples. Testing data using the IBM SPSS Statistic 25 program. This study obtained the following results: 1) Village original income (PADes) affects village financial independence positively and significantly, 2) Village fund allocation (ADD) affects village financial independence negatively and significantly, 3) Simultaneously allocation of funds village (ADD) and village original income (PADes) significantly affect village financial independence.